Social marketing for counseling and testing center: a case-study in the Oswaldo Cruz Policlinics, Porto Velho – RO - Tibúrcio, Adriana A.C.; Tibúrcio, Alberto S. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the social marketing is a strategy to change behaviors and its may be used in the promotion of the services that a Counseling andTesting Center offers. Objective: to verify the populational characteristics and opinions of a sample of CTC’s users, trying to recognize social marke-ting strategies for this type of health service. Methods: a questionnaire with ten questions was applied to the users looking for knowledge about pre-vention, quality of the service, and how they take information about the CTC. Results: 51.5% of the users had delayed more so than six months tolooking for consults; the ‘counseling’ it self was considered more important that the anti-HIV testing; 12.9% of users knowed what would occur du-ring the consult in the CTC; the ‘given attention’ to users and the ‘hygiene’ of installations were the more appreciated qualities; ‘males’ and ‘persons39-61 years old aged’ were the most satisfied with the service; television and newspapers are the ways through the users getting the news and infor-mation, but these users knew about CTC through friends, others users, health’s professionals and services. Conclusion: the social marketing is beingfew used to divulge the services given for CTC; the campaigns of public health may emphasize the CTC’s qualities in view of income the demand.